2014
DOI: 10.2298/mpns1408202n
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical analysis of sex-steroid receptors, tumor suppressor gene p53 and Ki-67 in the normal and neoplastic uterine cervix squamous epithelium

Abstract: The findings of this study suggest that tumor cervical cells evade normal growth control by sex steroid hormones while synchronously abnormal regulatory mechanisms acquire control of the cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…ER-a and PR have previously been identified as prognostic markers in assessing breast cancer in humans with loss of expression of ER-a and/or PR indicating poor prognosis [22,23]. In human cervical cancer, a study had similar results to those in sea lions with loss of ER expression but increased PR expression in IEN [24]. Studies in other animals have identified similar associations.…”
Section: Aetiology Of Urogenital Carcinoma In the California Sea Lionmentioning
confidence: 71%
“…ER-a and PR have previously been identified as prognostic markers in assessing breast cancer in humans with loss of expression of ER-a and/or PR indicating poor prognosis [22,23]. In human cervical cancer, a study had similar results to those in sea lions with loss of ER expression but increased PR expression in IEN [24]. Studies in other animals have identified similar associations.…”
Section: Aetiology Of Urogenital Carcinoma In the California Sea Lionmentioning
confidence: 71%
“…Unlike epithelial ERα that diminishes during CC progression (Nonogaki et al 1990, Konishi et al 1991, Coelho et al 2004, Zhai et al 2010, Nikolaou et al 2014, den Boon et al 2015, stromal ERα continues to persist during the course of CC progression (den Boon et al 2015). Findings from both in vivo studies and experiments conducted with clinical specimens appear to be very consistent.…”
Section: Maintenance Of Erα Expression In Tumour Stromamentioning
confidence: 76%
“…Contrary to the above statement, the loss of ERα expression was established as an early alteration during the progression of cervical dysplasia to invasive carcinoma (Nonogaki et al 1990, Konishi et al 1991, Coelho et al 2004, Zhai et al 2010, López-Romero et al 2013, Nikolaou et al 2014. The majority of the basal cells in normal cervical tissue stained positive for ERα, whereas the percentage of ERα expression was decreased in CIN and squamous cervical carcinoma to 31% and 11%, respectively (Nikolaou et al 2014). In contrast, PR expression tends to increase alongside CC progression with 29% for CIN and 49% for CIN and squamous cervical carcinoma.…”
Section: Studies Using Clinical Specimens Indicate a Differential Erαmentioning
confidence: 93%
See 2 more Smart Citations